2015
DOI: 10.1002/pon.3814
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of undergoing genetic-risk profiling in men with a family history of prostate cancer

Abstract: Personalised genetic-risk assessments do not prevent men from overestimating their risk of PrCa. Screening anxiety is common, and timeframes for receiving results should be kept to a minimum. Methods of risk communication in men at risk of PrCa should be the subject of future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 42 publications
1
31
1
Order By: Relevance
“…Evidence supports the theory that genetic testing for BRCA1 and BRCA2 mutations does not have a significant long‐term psychological impact on most people tested . Studies in men undergoing PCa screening suggest that a minority experience some anxiety, usually while waiting for results . Risk factors for anxiety include having a family history of PCa, symptoms or abnormal genetic test results .…”
Section: Introductionmentioning
confidence: 90%
“…Evidence supports the theory that genetic testing for BRCA1 and BRCA2 mutations does not have a significant long‐term psychological impact on most people tested . Studies in men undergoing PCa screening suggest that a minority experience some anxiety, usually while waiting for results . Risk factors for anxiety include having a family history of PCa, symptoms or abnormal genetic test results .…”
Section: Introductionmentioning
confidence: 90%
“…There is more to the development of disease than genetics alone, with lifestyle factors also having significant influence on risk. Several studies have found that regardless of risk perception, being given a personal polygenic risk score for risk of breast or prostate cancer did not have an impact on emotional state …”
Section: Targeted Cancer Screeningmentioning
confidence: 99%
“…It is important to be attentive to emotions and consider genetic risk discussions as a two‐way conversation rather than one‐sided information giving . Clinicians should be mindful that a person's life experience will influence their interpretation of risk, and research has shown that people do not change these risk perceptions when provided with new risk information; it may have some impact, but life experience plays the larger role . Patients with cancer often have theories about why they were diagnosed and wonder about the impact of lifestyle factors.…”
Section: What Will Be the Role Of Clinical Genetics Teams In The Future?mentioning
confidence: 99%
See 2 more Smart Citations